Economic category «library service» in the conceptual terminology of library science - D. M. Tsukerblatt (Библиосфера)
The author considers key questions for establishing the economic category «library service» in professional library terminology. Materials of ongoing discussions on the impact of social and cultural factors on economic development and the role of libraries in meeting information needs of science, education and business are analyzed. The most important tasks on interaction between actors in providing library services, formulated as assistance in forming readers’ knowledge and person development.